Twelve weeks of hiking training improves heart rate variability and cardio-respiratory endurance in women with panic disorder - Nahid Ashkriz; Lotfali Bolboli; Mostafa Khani; Roghayyeh Afroundeh; Mahta Eskandarnejad (Sport Sciences and Health Research)
Background: Heart rate variability (HRV) as a non-invasive indicator measures the activity level of the autonomic nervous system. Exercise has significant positive effects in increasing HRV indicators, which ultimately leads to cardiovascular health. People with panic disorder (PD) generally have low HRV indices and are more exposed to cardiovascular risks.Aim: The aim of the present study is investigating the effect of 12 weeks of hiking training on HRV of women with PD.Materials and Methods: In this semi-experimental clinical trial, 18 women with PD with average panic scores (45.00±19.55) as determined by Albany Panic and Phobia Questionnaire (APPQ) in two training group (12 weeks of hiking training with 70% to 80% MHR, three sessions a week, each one an-hour, and control group (without any regular physical activity) participated randomly. HRV of subjects was measured by Holter monitoring device (with 7 leads VX3+ SN 17570 made in USA) while resting and lying back for 20 min before and after 12 weeks.Results: The results of covariance analysis showed that panic scores (P≤0.001) and HRV factors including: SDNN (P≤0.05), SDNN index (P≤ 0.01) and TP (P≤0.03) of the subjects in the training group improved significantly but HF, LF, LF/HF, did not show significant changes (P≥0.05).Conclusion: It seems that 12 weeks of hiking training improves some of the HRV indices of women, which prevents the risk of cardiovascular diseases, and also reduces the symptoms of panic in women.